Strut-and-tie approach to shear strength prediction of deep beam - Tong, Ke Bo. (2009)
The studies in this thesis mainly focus on the strut-and-tie approach to shear strength prediction of deep beam. Both the non-prestressed and prestressed deep beams as well as deep beams with web openings are considered. Different from the previous studies in this field, the new strut-and-tie approach is based on the conventional theories of failure, i.e., Mohr-Coulomb's criterion and Kupfer's criterion. Furthermore, the new approach can be derived from first principles and it contains little empiricism.